2021
DOI: 10.1096/fj.202101169r
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial‐induced oral dysbiosis exacerbates naturally occurring alveolar bone loss

Abstract: Periodontitis-mediated alveolar bone loss is caused by dysbiotic shifts in the commensal oral microbiota that upregulate proinflammatory osteoimmune responses.The study purpose was to determine whether antimicrobial-induced disruption of the commensal microbiota has deleterious effects on alveolar bone. We administered an antibiotic cocktail, minocycline, or vehicle-control to sex-matched C57BL/6T mice from age 6-to 12 weeks. Antibiotic cocktail and minocycline had catabolic effects on alveolar bone in specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…We developed a novel murine oral antiseptic rinse model, which revealed the commensal oral microbiota promote the activation of oral helper T‐cells to affect osteoblast–osteoclast actions in alveolar bone (Hathaway‐Schrader, Aartun, et al, 2022). Further, we demonstrated that antibiotic‐induced shifts in commensal oral microbiota can dysregulate helper T‐cell oral immunity to have catabolic effects on alveolar bone remodelling (Swanson et al, 2021). Central to this study, antibiotic prophylaxis effects on microbiota–osteoimmune processes regulating dental implant placement surgery‐induced alveolar bone wound healing and osseointegration have not been investigated.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…We developed a novel murine oral antiseptic rinse model, which revealed the commensal oral microbiota promote the activation of oral helper T‐cells to affect osteoblast–osteoclast actions in alveolar bone (Hathaway‐Schrader, Aartun, et al, 2022). Further, we demonstrated that antibiotic‐induced shifts in commensal oral microbiota can dysregulate helper T‐cell oral immunity to have catabolic effects on alveolar bone remodelling (Swanson et al, 2021). Central to this study, antibiotic prophylaxis effects on microbiota–osteoimmune processes regulating dental implant placement surgery‐induced alveolar bone wound healing and osseointegration have not been investigated.…”
Section: Introductionmentioning
confidence: 91%
“…cytometry buffer. Cells were treated with FcR-block (Miltenyi Biotec, Bergisch Gladbach, Germany) and labelled for surface antibodies, per manufacturer's instructions as previously reported (Carson et al, 2023;Swanson et al, 2021). Dead cells were excluded via labelling with LIVE/ DEAD 405-nm Fixable Yellow Stain (Thermo Fisher Scientific), per manufacturer's instructions.…”
Section: S Gingival Bacteriome Analysismentioning
confidence: 99%
See 3 more Smart Citations